Dynamic Reconfigurable Computing: The Alternative to Homogeneous Multicores under Massive Defect Rates - Monica Magalhães Pereira; Luigi Carro (International Journal of Reconfigurable Computing)
The aggressive scaling of CMOS technology has increased the density and allowed the integration of multiple processors into a single chip. Although solutions based on MPSoC architectures can increase application's speed through TLP exploitation, this speedup is still limited to the amount of parallelism available in the application, as demonstrated by Amdahl's Law. Moreover, with the continuous shrinking of device features, very aggressive defect rates are expected for new technologies. Under high defect rates a large amount of processors of the MPSoC will be susceptible to defects and consequently will fail, not only reducing yield but also severely affecting the expected performance. This paper presents a run-time adaptive architecture that allows software execution even under aggressive defect rates. The proposed architecture can accelerate not only highly parallel applications but also sequential ones, and it is a heterogeneous solution to overcome the performance penalty that is imposed to homogeneous MPSoCs under massive defect rates.